Erratum: Muto, M., Chiba, T., Tuji, A., Horie, Y. & Fujibayashi, M. (2025) A new littoral diatom genus, Lyreneis gen. nov. (Bacillariophyceae, Lyrellales, Lyrellaceae), from southwestern Japan” Phytotaxa 711 (1): 1–27. - Muto, Mizuka; Chiba, Takashi; Tuji, Akihiro; Horie, Yoshifumi; Fujibayashi, Megumu (Phytotaxa, 2025)
Erratum